Über den Körper hinaus - Xue, Yuan (transcript, 2014)
Entfalten zeitgenössische Romane neue Konstruktionskonzepte von Körper und Subjekt?Dieses Buch befasst sich mit Geschlechterkonstruktionen, die sich von den bisher vorherrschenden poststrukturalistischen Denkmodi unterscheiden: Anhand deutscher, polnischer, kroatischer, finnischer und französischer Romane ab Ende der 1990er Jahre erstellt Yuan Xue eine angemessene Interpretationsweise für die neuartigen literarischen Erscheinungen. Sie bietet ein breites Spektrum an behandelter Literatur jenseits des Mainstreams und betritt so vielfach Neuland. Do contemporary novels develop new design concepts of the body and the subject? This book deals with gender constructions that differ from the previously prevailing poststructuralist modes of thinking: By reference to German, Polish, Croatian, Finnish, and French novels from the late 1990s, Yuan Xue creates an apt interpretive manner for application to new literary phenomena. This deals with a wide spectrum of literature beyond the mainstream and enters many uncharted territories.
Dissertation, Ludwig-Maximilians-Universität München, 2013
Keywords: Hochschulschrift; gender; gender studies; Literature; Body; Literary Studies; Gender Studies; Gender; literature; body; literary studies; Körper; Geschlecht; Literaturwissenschaft; Subjekt; Poststrukturalismus; Allgemeine Literaturwissenschaft; Roman; General Literature Studies; Post-structuralism; Literatur; Roman; Gender; Subjekt; Poststrukturalismus; Geschlecht; Körper; Allgemeine Literaturwissenschaft; Gender Studies; Literaturwissenschaft; Literature; Post-structuralism; Body; General Literature Studies; Literary Studies